PATTERN OF ETHNOMATHEMATICS RESEARCH TOWARDS HISTORICAL BUILDINGS - Arifin Riadi; Turmudi Turmudi; Dadang Juandi (Ethnomath Association in cooperation with Universitas Negeri Yogyakarta, 2025)
Historical buildings are very useful for discovering mathematical concepts for educational purposes. This literature review aims to identify (1) the mathematical concepts that have not emerged in the exploration of historical buildings and (2) the research design most frequently used in ethnomathematics studies related to historical buildings. Using the PRISMA protocol, a total of 64 articles were analysed. The research primarily explores traditional houses, but also includes studies on other architecture like mosques, tombs, temples, museums, and monuments. The research results indicate that (1) the mathematical concept that has not emerged in the exploration of historical buildings is Number and Operations and (2) the most frequently used research design in ethnomathematics exploration studies for historical buildings is the ethnographic design. This review highlights the importance of expanding the scope of ethnomathematical studies both geographically and conceptually, and suggests potential applications in mathematics education to enhance cultural relevance. The study contributes to the preservation of local heritage by linking cultural practices with mathematical principles, offering valuable insights for both academic research and educational practice.